Clinical distribution of carbapenem genotypes and resistance to ceftazidime-avibactam in Enterobacteriaceae bacteria - Xueyun Zhu; Xueyun Zhu; Caixia Guo; Shengxi Xu; Fei Lv; Zhusheng Guo; Sisi Lin; CongZhu Yang; Zhuliang Deng; Shaofeng Chen; Ya Huang; Zuguo Zhao; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionBacterial resistance is a major threat to public health worldwide. To gain an understanding of the clinical infection distribution, drug resistance information, and genotype of CRE in Dongguan, China, as well as the resistance of relevant genotypes to CAZ-AVI, this research aims to improve drug resistance monitoring information in Dongguan and provide a reliable basis for the clinical control and treatment of CRE infection.MethodsVITEK-2 Compact automatic analyzer was utilized to identify 516 strains of CRE collected from January 2017 to June 2023. To determine drug sensitivity, the K-B method, E-test, and MIC methods were used. From June 2022 to June 2023, 80 CRE strains were selected, and GeneXpert Carba-R was used to detect and identify the genotype of the carbapenemase present in the collected CRE strains. An in-depth analysis was conducted on the CAZ-AVI in vitro drug sensitivity activity of various genotypes of CRE, and the results were statistically evaluated using SPSS 23.0 and WHONET 5.6 software.ResultsThis study identified 516 CRE strains, with the majority (70.16%) being K.pneumoniae, followed by E.coli (18.99%). Respiratory specimens had highest detection rate with 53.77% identified, whereas urine specimens had the second highest detection rate with 17.99%. From June 2022 to June 2023, 95% of the strains tested using the CRE GeneXpert Carba-R assay possessed carbapenemase genes, of which 32.5% were blaNDM strains and 61.25% blaKPC strains. The results showed that CRE strains containing blaKPC had a significantly higher rate of resistance to amikacin, cefepime, and aztreonam than those harboring blaNDM.ConclusionsThe CRE strains isolated from Dongguan region demonstrated a high resistance rate to various antibiotics used in clinical practice but a low resistance rate to tigecycline. These strains produce Class A serine carbapenemases and Class B metals β-lactamases, with the majority of them carrying blaNDM and blaKPC. Notably, CRE strains with blaKPC and blaNDM had significantly lower resistance rates to tigecycline. CAZ-AVI showed a good sensitivity rate with no resistance to CRE strains carrying blaKPC. Therefore, CAZ-AVI and tigecycline should be used as a guide for rational use of antibiotics in clinical practice to effectively treat CRE.